Managing Complications in Glaucoma Surgery - Carbonaro, Francis; Lim, K. Sheng; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This well-illustrated book is intended as the go-to guide for the identification and management of the complications associated with specific glaucoma procedures. All of the routinely performed procedures are covered: filtration surgery, including trabeculectomy and ExPRESS shunt, nonpenetrating surgeries such as deep sclerectomy and canaloplasty, procedures involving the placement of tube shunt devices, glaucoma laser treatments, and minimally invasive glaucoma surgeries (MIGS). The book is succinct but sufficiently detailed to provide the reader with a very well informed description of possible complications and the best way to manage them, based on the evidence from recent and seminal research. The authors are recognized experts who come from a wide geographic and varied glaucoma background. The book will be ideal for all surgeons, whether new or experienced, who seek easily accessible, reliable guidance on how to manage the intraoperative and early and late postoperative complications that may arise when performing glaucoma surgery.
Complications in Glaucoma Laser -- Minimally-invasive glaucoma surgery -- Non-penetrating Glaucoma Surgery (Deep Sclerectomy, Viscocanaloplasty and Canaloplasty) -- Trabeculectomy complications and their management -- Complications associated with Glaucoma Tube Surgery.
Keywords: Medicine; Ophthalmology; Minimally invasive surgery; Medicine & Public Health; Ophthalmology; Minimally invasive surgery